Risk Evaluation and Mitigation Strategies for Potential Outbreaks of Adenovirus Infection: Evidence From the Recent Incidences in West Bengal, India - Rapty Sarker; ASM Roknuzzaman; Nazmunnahar; Md. Rabiul Islam (Clinical Pathology, 2023)
Recent outbreaks of highly virulent and pathogenic viruses such as COVID-19, monkeypox, and Nipah virus have prompted global concerns. Another threat has emerged in West Bengal, India, in the form of Human Adenovirus (HAdV), particularly affecting children and immunocompromised individuals. The DNA virus HAdV can cause respiratory, liver, renal, and neurological issues. Politically unstable areas with military and medical camps and refugee communities are at risk because they spread in densely populated areas. Due to its rapid mutation and dissemination, the virus represents a global threat. Although scientists have developed vaccines for specific serotypes of HAdV, their primary application is limited to military contexts. Antiviral and immunotherapy research is continuing, but treatment choices are limited. Public awareness programs and hygiene measures are essential to preventing a global pandemic. Governments should invest in healthcare infrastructure and diagnostics, and researchers should focus on developing vaccines and therapies. The West Bengal outbreak is a clear reminder that governments, healthcare professionals, and researchers must work together to control and prevent HAdV. To effectively comprehend and address this rising viral threat, it is imperative to engage in further research and documentation.